A Statistical Analysis of Book Publishing Industry in Ukraine: 1917–2017 - Horobets, О. О. (Statistics of Ukraine, 2019)
A broad statistical analysis of the book publishing industry over 1917–2017 is performed, with focus on the dynamics of industry indicators in 1991–2017. It is shown that throughout this period the average annual growth in the number of books and brochures produced by the book publishing industry made 620 units, or 5.13%. But the circulation had overall negative dynamics: its average annual decline made 3310 thousand, or 3.9%. The largest absolute decline in the circulation is recorded in 1993, 1999, and 2015. It is revealed that the per capita output in the industry was 1.5 books in 2013, 0.8 in 2015, and 1.1 in 2017. It is stressed that because books constitute a culture component and contribute in the moral enrichment of the society and book reading enhance the education level of a nation, the book supply of the population observed throughout the period of the Ukraine’s independence is unacceptable. A fact raising concern is that reading ranks fifth as a way of recreation in the Ukrainian society. It is demonstrated that the assumption about minor significance of a printed book in the digital era is fallacious and ungrounded. Transformations in science and technology, politics or economy have been persisting in Ukraine, but its people remain to be book readers. A book may change the format or production methods and materials, but a book is an integral attribute of the humanity. The events in Ukraine, both positive and negative, had strong impact on the development and change of socio-economic paradigms, which had implications for the book publishing industry. The development of any industry cannot be considered in isolation, by taking its dynamics off the context of socio-political processes and phenomena. It is shown that in the present-day conditions, when the living standards of the population are largely dependent on the salary rate or the household income, the need to purchase books had lower priority than meeting vital necessities of daily life. The importance of a further in-depth study of the external factors with impact on the industry development is stressed.